Gorenstein tiled orders - Kiricenko, V.; Khibina, M.; Mashchenko, L.; Plakhotnyk, M.; Zhuravlev, V. (Carpathian Mathematical Publications, 2014)
The aim of this article is to describe exponent matrices of Gorenstein tiled orders. The necessary and sufficient condition for possibility such to construct a Gorenstein tiled order which has given orders over some discrete valuation ring (the unique for the whole main diagonal) on the main diagonal and its permutation be a product of correspond cycles with given cyclic Gorenstein tiled order is considered.